Genetic Study of Elf5 and Ehf in the Mouse Salivary Gland. (March 2023) - Song, E.A.C.; Smalley, K.; Oyelakin, A.; Horeth, E.; Che, M.; Wrynn, T.; Osinski, J.; Romano, R.A.; Sinha, S.
Salivary gland (SG) development, maturation, and homeostasis require coordinated roles of transcription factors (TFs) that dictate specific cell identities and fate. The ETS family of proteins are important transcriptional drivers of diverse cell lineages, tissue development, and differentiation programs and hence are also likely to play an important role in the SG. Here we have leveraged genomic and epigenomic data of the SG to examine the expression profile of ETS genes and identified 2 closely related paralogs, Elf5 and Ehf, that are highly expressed in distinct epithelial subpopulations. By using a well-defined mouse knockout model of Elf5, we show that Elf5, despite its enriched expression in the acinar cells, is functionally dispensable for maintaining the homeostatic state of the adult SG epithelium. The lack of a discernible phenotype of the Elf5-null SG might be due to possible functional redundancy with Ehf or other ETS factors. To probe this possibility and to examine the specific consequences of Ehf loss in the SG, we used CRISPR-Cas9 to generate mice in which the DNA-binding ETS domain of Ehf is disrupted due to an insertion mutation. We demonstrate that the Ehf mutant (EhfMut) mice exhibit a distinct cellular phenotype with decreased granular convoluted tubules that are accompanied by an increased accumulation of the intercalated Sox9-positive ductal cell population. Interestingly, the ductal phenotype of the EhfMut animals is highly pronounced in males, reaffirming the established sexual dimorphism of the SG that exists in rodents. Our results show that unlike Elf5, Ehf plays a nonredundant role in directing ductal cell differentiation of the SG and highlights the phenotypic subtlety in mutant mice of closely related TFs and the importance of careful consideration of cell type–specific studies.